DOI: 10.32657/10356/50919
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neuro-fuzzy inference system for flood forecasting in a large river system

Abstract: Large river systems provide essential water resources and economic benefits for a significant number of people. However, large floods that occur less frequently (e.g., 25 to 100-year floods) can cause significant loss of lives and property. Therefore, flow forecasting, which aims to provide accurate forecasts of flow and/or level of a river is an essential tool for flood plain management and flood mitigation purposes. New approaches in computational intelligence tools are now being applied to build effective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…is a data-driven model such as ANN; IC i is formed by a number of input candidate pools X n (t -1, t -2,..., t -i) where X n generally indicates previous observation of SPEI, rainfall or CIs, and t -i indicates lagged time of the above-mentioned variables. We selected i = 3 as maximum lagged time for local candidates [31] and i = 12 as maximum lagged time for CIs [32].…”
Section: Drought Forecasting Flowchartmentioning
confidence: 99%
“…is a data-driven model such as ANN; IC i is formed by a number of input candidate pools X n (t -1, t -2,..., t -i) where X n generally indicates previous observation of SPEI, rainfall or CIs, and t -i indicates lagged time of the above-mentioned variables. We selected i = 3 as maximum lagged time for local candidates [31] and i = 12 as maximum lagged time for CIs [32].…”
Section: Drought Forecasting Flowchartmentioning
confidence: 99%
“…The outcome of the study found the ANN model capable of predicting the SPEI and SPI over the considered area. Nguyen et al [11] focused on the prediction of drought at short-term and long term basis in Cai river basin, Vietnam using the ANFIS model; the prediction was based on SPI & SPEI. From the result, SPI and SPEI were found useful in predicting short-and long-term drought, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the impact of drought, an effective and timely monitoring system is required, the effective monitoring of drought can aid in the development of an early warning system [17]. At present a lot of models have been accepted as efficient tools for the modeling of complex hydrologic systems widely employed for forecasting, such as artificial neural networks (ANNs) and autoregressive moving average approach (ARMA) [18][19][20].…”
mentioning
confidence: 99%